Das atmende Klarsein: Per piccolo coro, flauto basso, live electronics e nastro magnetico - Nono, Luigi 1924-1990; Cacciari, Massimo (Milan Ricordi, 2005)
Researching into the fringe ranges of hearing, and actually going to the limits: electronics – live or prerecorded – was one of the tools employed by Luigi Nono in pursuance of this object. In his work Das atmende Klarsein he moreover endeavored to expand the ability of listening: "Waking up the ear, the eyes, human understanding, intelligence, is what is essential today," the composer, also a politically aware man, observed in the early 1980s. Das atmende Klarsein "is a key work of Nono's final years as regards his vocal technique and the use of live electronics in view of the transformation of instrumental sounds, in this case the bass flute." (Max Nyffeler) The composition ...sofferte onde serene... reflects Nono's friendship with Maurizio Pollini and their shared history of "serene waves endured." Like Con Luigi Dallapiccola it is one of Nono's intimate and personalized compositions that are essentially addressed to one recipient only.
Testi da Duineser Elegien di Rainer Maria Rilke e da antiche lamellae orfiche a cura di Massimo Cacciari (1980-83)